Food for thought: how nutrition impacts cognition and emotion. (December 2017) - Spencer, Sarah; Korosi, Aniko; Layé, Sophie; Shukitt-Hale, Barbara; Barrientos, Ruth
Abstract More than one-third of American adults are obese and statistics are similar worldwide. Caloric intake and diet composition have large and lasting effects on cognition and emotion, especially during critical periods in development, but the neural mechanisms for these effects are not well understood. A clear understanding of the cognitive–emotional processes underpinning desires to over-consume foods can assist more effective prevention and treatments of obesity. This review addresses recent work linking dietary fat intake and omega-3 polyunsaturated fatty acid dietary imbalance with inflammation in developing, adult, and aged brains. Thus, early-life diet and exposure to stress can lead to cognitive dysfunction throughout life and there is potential for early nutritional interventions (e.g., with essential micronutrients) for preventing these deficits. Likewise, acute consumption of a high-fat diet primes the hippocampus to produce a potentiated neuroinflammatory response to a mild immune challenge, causing memory deficits. Low dietary intake of omega-3 polyunsaturated fatty acids can also contribute to depression through its effects on endocannabinoid and inflammatory pathways in specific brain regions leading to synaptic phagocytosis by microglia in the hippocampus, contributing to memory loss. However, encouragingly, consumption of fruits and vegetables high in polyphenolics can prevent and even reverse age-related cognitive deficits by lowering oxidative stress and inflammation. Understanding relationships between diet, cognition, and emotion is necessary to uncover mechanisms involved in and strategies to prevent or attenuate comorbid neurological conditions in obese individuals.